A new species of Cyphocarididae (Crustacea, Amphipoda, Lysianassoidea) from off the northeastern Brazilian coast - Sorrentino, Rayane; Alves, Jessika; Johnsson, Rodrigo; Senna, André R. (Zootaxa, 2016)
This paper describes a species of the genus Cyphocaris Boeck, 1871, the first record of the family Cyphocarididae Lowry & Stoddart, 1997 from Brazil. Two specimens, both females, were found in the stomach contents of a tuna caught in the Saint Peter and Saint Paul Archipelago. The new species is characterized by coxae 4 and 5 both large, coxa 4 partially overlapping coxae 2–3; coxa of pereopod 5 with ventral laminar projection and well-developed anteroventral lobe, broadly rounded and apically folded backwards, basis with anterior margin broadly rounded and posterior margin with large subacute naked projection (or spur); uropod 3, outer ramus paddle-shaped; and telson elongate and deeply cleft, with a nail.